Model Kepemimpinan Indigenous dan Penguatan Human Capital di UMKM Perawatan Sepatu - Choirul Anam; Survival Survival; Wahju Wulandari (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
SMEs are the backbone of the local economy and require contextualized and adaptive leadership and human capital management strategies. This article aims to describe the indigenous values-based leadership model implemented in Aglaia Shoes Cleaning-a shoe-care SME in Malang City-and how it contributes to strengthening human capital. The service activities were carried out through a participatory and educative approach, including soft skills training, structuring work structures, and preparing simple SOPs based on local cultural values such as mutual cooperation, responsibility, and perseverance. The results of the activities show that a leadership approach that integrates indigenous values can create a more collaborative work environment, increase productivity, and foster loyalty and a sense of ownership in the work team. Strengthening human capital does not only occur through increasing technical capacity, but also through instilling local values and work ethics. This model has the potential to be replicated in other MSMEs with similar characteristics to encourage local culture-based business sustainability.